a study on trichomonas vaginalis and comparison between the efficacy of metronidazole and secnizole on women in Kirkuk province - Kadir, Mohammed A.; Ghalib, Ayla Kh.; Tahir, suheila SH.; AL-Dalableh, fayez (Journal of the Faculty of Medicine Baghdad, 2006)
Background: